Peoples, cultures, and nations in political philosophy - Gilbert, Paul, 1942- (University Press, 2000)
"Wars of national secession and ethnic cleansing have disfigured recent years. These conflicts stem from claims that the same territory is occupied by separate 'peoples' for whom separate political arrangements should be made. Such claims are based on their supposedly distinct racial, ethnic, cultural or national identities. What, though, do such identities really amount to and what ought to be their role in determining the configuration and character of states? This has become a key concern of contemporary political philosophy and this book introduces readers to the materials required to address it." "This is the first comprehensive survey of a highly topical issue and its multidisciplinary approach will make it of relevance to courses in philosophy, politics, sociology and cultural studies, as well as of interest to the general reader."--Jacket